Latent factors That affect applicants’ choice of the University of Cape Coast - Inkum, Ivy Eyiah (University of Cape Coast, 2012)
Choice of university education in Ghana is a competitive exercise for Senior High School students. Choosing it requires consideration of various factors. The motivation for the study is to measure high school students’ perception of the University of Cape Coast. To this end, the study focuses on various factors. The objective of the study therefore is to determine the latent factors that are considered by the SHS students in their decision. In order to achieve this objective, 20 Senior High Schools were selected for the study. A questionnaire was used to that effect. The hypotheses related to the thesis lie in the choice and significance of the factors the students used to answer the 28 indicators. The main analytical technique used in the study is factor analysis. After rotation, the main latent factor influencing applicants’ choice of the University of Cape Coast is academic resources. Four other factors in decreasing order of influence are quality assurance, cost of study, influences of others and discipline. It is worth mentioning that almost all the factors are dependent on some demographic characteristic such as age and sex of the respondents.
x, 141p:,ill.
Keywords: Senior High School; motivation; Hypotheses; Analytical technique